A reduced transferrin saturation is independently associated with excess morbidity and mortality in older adults with heart failure and incident anemia. (15th June 2020) - Ambrosy, Andrew P.; Fitzpatrick, Jesse K.; Tabada, Grace H.; Gurwitz, Jerry H.; Artz, Andrew; Schrier, Stanley L.; Rao, Sunil V.; Reynolds, Kristi; Smith, David H.; Peterson, Pamela N.; Fortmann, Stephen P.; Sung, Sue Hee; et al.
Abstract: Background: Low transferrin saturation (TSAT) or reduced serum ferritin level are suggestive of iron deficiency but the relationship between iron parameters and outcomes has not been systematically evaluated in older adults with heart failure (HF) and anemia. Methods: We identified a multicenter cohort of adults age ≥ 65 years with HF and incident anemia (hemoglobin <13 g/dL [men] or < 12 g/dL [women]) between 2005 and 2012. Patients were included if ferritin (ng/mL) and TSAT (%) were evaluated within 90 days of incident anemia. HF hospitalizations and all-cause death were ascertained from electronic health records. Results: Among 4103 older adults with HF and incident anemia, 47% had TSAT <20% and the median (IQR) ferritin was 126 (53, 256) ng/mL. In multivariable analyses, compared with TSAT ≥20%, patients with TSAT <20% were at increased risk of HF hospitalization for serum ferritin <100 ng/mL (adjusted HR [aHR] 1.40, 95% CI:1.16–1.70) and 100–300 ng/mL (aHR 1.24, 95% CI:1.01–1.52) but not for a ferritin >300 ng/mL (aHR 0.89, 95% CI 0.65–1.23). In addition, TSAT <20% was independently associated with an increased risk of all-cause death regardless of serum ferritin level (<100 ng/mL: aHR 1.42, 95% CI:1.20–1.68; 100–300 ng/mL: aHR 1.18, 95% CI:1.00–1.38; >300 ng/mL: aHR 1.33, 95% CI:1.06–1.69). Conclusions: Among older adults with HF and incident anemia who had iron studies tested, nearly half had a TSAT <20%, which was independently associated with higher rates of morbidity and death. Highlights: Among older adults with HF, 55% of patients were found to have iron deficiency (i.e., ferritin <100 ng/mL or ferritin 100–300 ng/mL and TSAT <20%). A TSAT <20% was independently associated with HF hospitalizations and all-cause death. These findings remained unchanged in sensitivity analyses stratified by degree of systolic dysfunction (i.e., reduced vs. mid-range vs. preserved).